First appearance deceives many: disentangling the Hemidactylus triedrus species complex using an integrated approach - Mirza, Zeeshan A. (PeerJ, 2018)
The gekkonid lizard genus Hemidactylus Oken is the second most species-rich genus of geckos with greatest diversity in the tropical regions of the world. Some species of the genus are commensal and widespread; however, there are several endemic lineages with restricted distribution. India is home to at least 35 species, with 20 endemic species and the number is steadily increasing with exploration of new habitats and integrated taxonomic approach including molecular data. We made investigations into the molecular and morphological variation throughout the distribution of Hemidactylus triedrus Daudin, 1802 based on fresh specimens, literature review, museum material and molecular data. Results from morphological, molecular and micro-CT based anatomical data are unequivocal and show that H. triedrus is a species complex represented by three species, H. triedrus sensu stricto and two undescribed taxa. H. subtriedrus Jerdon, 1854 syn. nov. was found to be morphologically similar to the type specimen of H. triedrus, and genetically embedded in a clade containing H. triedrus sensu stricto and is here treated as a junior synonym of H. triedrus, whereas H. lankae Deraniyagala is referred to as nomen dubium given that the types are presently not traceable and the original description is inadequate in diagnosing the taxon. The populations from western-central India and parts of Pakistan, and from southern Karnataka are distinct and diagnosable, and are herein described as two new species, respectively. Morphological and molecular data support the distinctiveness of the new species. The present work resolves a taxonomic turmoil that lasted over two centuries highlighting the need for studies that integrate morphological and molecular data.